2015
DOI: 10.1142/s0217984915501390
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on the band structure, magnetic and elastic properties of half-metallic Cr2MnAl

Abstract: In this study, we have investigated the structural, electronic, magnetic and elastic properties of the full-Heusler Cr 2 MnAl alloy in the framework of density functional theory with generalized gradient approximation (GGA). The calculated results showed that Cr 2 MnAl was stable in ferrimagnetic configuration and crystallized in the Hg 2 CuTitype structure. From the band structure and density of states calculation results, we concluded that Cr 2 MnAl belongs to a kind of half-metallic compound with an indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The shear modulus (G) depicts the resistance of a material to shape change, while the Young modulus determines the resistance against uniaxial tensions. These parameters are important factors to define the mechanical features of a material [35]. We notice that there are no available data to compare with our results of elastic constants, bulk, and shear modulus.…”
Section: Elastic Properties and Mechanical Stabilitymentioning
confidence: 78%
See 2 more Smart Citations
“…The shear modulus (G) depicts the resistance of a material to shape change, while the Young modulus determines the resistance against uniaxial tensions. These parameters are important factors to define the mechanical features of a material [35]. We notice that there are no available data to compare with our results of elastic constants, bulk, and shear modulus.…”
Section: Elastic Properties and Mechanical Stabilitymentioning
confidence: 78%
“…The study of the elastic properties has an important role to know the nature of the bond between the neighbouring atomic planes, and the elastic constants describing the mechanical stability of the deformation of the crystalline face. It is the proportionality coefficients connecting the applied strain to the stress, which give the response of the material, its strength and mechanical stability under compression [12,34,35]. The computed elastic constants C 11 , C 12 , and C 44 are summarized in Table II.…”
Section: Elastic Properties and Mechanical Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] 0 5.760 0.38 Expt. [ 15 ] 0 5.770 0.55 GGA [ 20 ] 0 5.738 188.958 228.21 GGA This work 5 5.69 184.220 230.18 10 5.66 181.321 257.97 15 5.62 177.504 290.71 20 5.59 174.677 307.98 25 5.56 171.880 313.73 30 5.53 169.112 331.98 Cr 2 MnAl 0 5.831 0.99 GGA [ 5 ] 0 5.850 0.67 GGA [ 17 ] 0 5.866 141.83 0.39 GGA [ 22 ] 0 5.889 204.23 125.29 GGA This work 5 5.82 197.137 159.67 10 5.77 192.100 186.68 …”
Section: Resultsmentioning
confidence: 99%
“…Another computational study showed that Cr 2 CoAl is a compensated half-metal (CHM) [ 21 ]. There is a DFT study which confirms the half metallicity of Cr 2 MnAl [ 22 ]. According to this study, the magnetic moment calculation of Cr 2 MnAl is consistent with Slater-Pauling rule.…”
Section: Introductionmentioning
confidence: 95%